A tragedy tailored to the spirit of the times – Romeo and Juliet as interpreted by Franco Zeffirelli and Baz Luhrmann - Śliwińska, Anna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2019)
This article discusses two film adaptations of Romeo and Juliet, i.e. one directed by Franco Zeffirelli and the other by Baz Luhrmann. It covers the following aspects: the structure of both the drama and its two film adaptations, the characters’ creation, the choice of setting and screen time, and the function of tragedy. Shakespeare’s language is characterised by unparalleled wit and powers of observation, and the final form of his plays is a clear indication of his ambivalent attitude towards tradition and the rigid structure of the drama. By breaking with convention, favouring an episodic structure, and blending tragedy with comedy, Shakespeare always takes risks, in a similar vain to the two directors who decided to make film adaptations based on his plays. Each technical device the adaptors selected could have turned out to be a wonderful novelty or a total disaster. The strength of both Zeffirelli’s and Luhrman’s adaptations is their emphasis on love and youth, which thanks to their directorial skill is perfectly in tune with the spirit of their respective times.